Effect of different targeted calyxes on the treatment of multi-site calculi in the postural drainage lithotripsy system - Yang, Tao; Wu, Chong; Dai, Liangliang; Hu, Zhixiong; Song, Rijin; Meng, Xianghu; Shi, Honglei (Frontiers in Medicine, 2023)
Abstract Objectives We developed a Postural Drainage Lithotripsy System (PDLS) that can provide an individualized inversion and overturning angle and uses gravity to remove the residual fragments (RFs). This study aimed to evaluate the effect of different targeted calyces on treating multi-site stones in PDLS. Methods 20 stones with different sizes and diameters of 0-4mm were placed in the kidney model through ureteroscopy, and 20 stones were evenly scattered in the middle and lower calyx of the model. The ventral-middle calyx, dorsal-middle calyx, ventral-lower calyx and dorsal-lower calyx were used as the targeted calyx of PDLS to treat multi-site stones. During treatment, if the stone moves from the starting position of the renal calyx to the ureteropelvic junction, it is recorded as passing through. The clearance rate was recorded and the efficacy of different targeted calices in the treatment of multiple site calculi was compared. Each model was treated with 4 different targeted calyces, and 20 models were tested 80 times. Results When the lower calyx was the targeted calyx, the total stone clearance rate was higher than that when the middle calyx was the locating calyx (94.5% vs 64%, P = 0.000, the result was statistically significant). Conclusions Choosing the lower calyx as the targeted calyx can obtain a better stone clearance rate. Still, there is no significant difference between the ventral lower calyx and the dorsal lower calyx. Keywords Residual fragment · Active lithecbole · Postural drainage · Urolithiasis · Individualized therapy